Misery loves company. Strategies for retrenchment in the era of constrained public finance. (16th August 2018) - Cavalieri, Alice; Russo, Federico; Verzichelli, Luca
Abstract: The policy agenda literature shows that budget cuts tend to be rarer and less extreme than budget expansions. This article argues that the character of retrenchment policies is shaped by a combination of domestic and international factors, such as budgetary procedures, intra-coalitional conflicts, and the emergence of urgency situations. Building on the findings of several quantitative studies on budgetary changes, we develop two propositions explaining why the necessity to reduce expenditures usually leads to across-the-board cuts. We also hypothesize two mechanisms which can occasionally produce selective outcomes. This article focuses on the last 30 years to observe how the annual package of public finance corrections has impacted on the main categories of public spending. This analysis combines an original measure of the transformative nature of the yearly fiscal packages approved by parliament with process-tracing methodology. The qualitative analysis focuses on three cases of linear cuts and one deviant case of selective cuts. Findings show that the persistence of frictions in the Italian budgetary process is often a basic reason for the introduction of linear cuts, but the logic of urgency triggered by the European external constraint was able to produce a selective outcome.